The vascular effects of peppermint (Mentha longifolia. L) on aorta in a mouse model: an ex-vivo and computational study - Alkharfy, Khalid M.; Ahmad, Ajaz; Almuaijel, Saleh; Hashim, Abdullah; Raish, Mohammad; Jan, Basit L.; Rehman, Najeeb Ur; Anwar, Farooq; Rehman, Md Tabish; Alajmi, Mohamad F. (Taylor and Francis, 2024)
The present study examined the vascular effects of peppermint or mint (Mentha longifolia L.) using an abdominal aortic rings model. Concentration-response curves for mint oil were generated after precontracting isolated mouse aorta with phenylephrine. The effect of different receptor antagonists and ion channel or enzyme inhibitors on the vasorelaxant potential of mint oil were studied. Molecular docking studies were conducted using computational techniques to investigate the potential interactions between the bioactive constituents of mint oil and key vascular targets. The tension of aortic rings, which had been contracted by phenylephrine, relaxed as a function of the concentration of mint oil (0.0002–2 mg/mL). Pretreatment of the rings with the nitric oxide synthase inhibitor (L-NAME), a nonselective β-blocker (propranolol), and a muscarinic receptor blocker (atropine) didn’t show significant resistance to the vasodilatory effects of the mint oil. The vasodilatory effects of mint oil were significantly diminished when the rings were pretreated with glibenclamide, an inhibitor of ATP-sensitive K+ channels. In addition, indomethacin, a cyclooxygenase (COX) inhibitor, did influence mint oil’s tension in the preparations precontracted with phenylephrine. The present findings imply that ATP-sensitive K+ channels activation, blocking of Ca2+ channels, and inhibition of COX play a role in mediating the mint oil-induced vasorelaxation. Molecular docking studies of mint oil constituents showed that β-Elemene and Aromadendrene can interact with K+ and Ca2+ channels through various hydrophobic interactions with key amino acid residues. Additional work is needed to confirm the possible beneficial application of mint oil or its constituents in regulating the vascular tone.